2020
DOI: 10.1242/jcs.247593
|View full text |Cite
|
Sign up to set email alerts
|

An indispensable role for dynamin-related protein 1 in beige and brown adipogenesis

Abstract: Emerging evidence indicates that proper mitochondrial dynamics is critical for adipocyte differentiation and functional thermogenic capacity. We found that mitochondrial fission protein dynamin-related protein 1 (DRP1) is highly expressed in brown adipose tissue compared to white adipose tissue and their levels increase during brown adipocyte differentiation. Our results reveal that the inhibition of DRP1 using Mdivi-1 mitigates beige adipocyte differentiation and differentiation-associated mitochondrial bioge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
(51 reference statements)
1
2
0
Order By: Relevance
“…Proper mitochondrial dynamics are critical for adipocyte thermogenesis and it was found that the mitochondrial fission protein dynamin-related protein 1 (DRP1) is highly expressed in the BAT and increases with the differentiation of the brown adipocyte. The inhibition of DRP1 expression attenuates mitochondrial biogenesis in beige adipocytes, which confirms that DRP1 plays an important role in beige and brown adipogenesis and thermogenesis 86 .…”
Section: Regulates Adipose Tissue Thermogenesis and Energy Metabolism...supporting
confidence: 59%
“…Proper mitochondrial dynamics are critical for adipocyte thermogenesis and it was found that the mitochondrial fission protein dynamin-related protein 1 (DRP1) is highly expressed in the BAT and increases with the differentiation of the brown adipocyte. The inhibition of DRP1 expression attenuates mitochondrial biogenesis in beige adipocytes, which confirms that DRP1 plays an important role in beige and brown adipogenesis and thermogenesis 86 .…”
Section: Regulates Adipose Tissue Thermogenesis and Energy Metabolism...supporting
confidence: 59%
“…Furthermore, DNM1 is overexpressed in brown adipose tissue, and its level escalates during beige and brown adipocyte differentiation. Inhibition of DNM1 expression was confirmed to mitigate beige adipocyte differentiation, thereby validating its essential role in beige and brown adipogenesis ( Mooli et al, 2020 ).…”
Section: Discussionmentioning
confidence: 76%
“…Although there was no change in mitochondrial DNA and PGC1α, the UCP1 levels were decreased and the DRP1 levels were increased in mice fed with a HFD. This suggested that it was a strong indicator of change from white adipose tissue to brown adipose tissue (i.e., UCP1 levels) and fission of mitochondria (i.e., DRP1 levels) (Shimokawa et al, 2019;Mooli et al, 2020). Interestingly, the treatment with PB mitigated mitochondrial fission and promoted browning of the white adipose tissue (Figure 4C).…”
Section: Resultsmentioning
confidence: 93%